Induction Shoots From Callus of Cucumber Apple (Cucumis sp.) Using a Combination of Benzil Amino Purine and Naphtalene Acetic Acid Concentrations In Vitro - Fransisca Natalia Erzalinda Mendrofa; Nurcahyo Widyodaru Saputro; Lutfi Afifah (Mangifera Edu, 2021)
Research on indirect organogenesis of cucumber apple (Cucumis sp.) was conducted from March to May 2020. This study aims to find the best combination between Benzyl Amino Purine (BAP) and Naphthalene Acetic Acid (NAA) on the growth of cucumber apple (Cucumis) sp.) on Gamborg media (B5) by organogenesis. The callus used came fromcucumber seeds explants with a concentration of NAA 2,0 mg/l + BAP 0,2 mg/l using Murashige and Skoog media. The research method used is an experimental method with nonparametric statistics with 24 treatments repeated three times and analyzed descriptively using the Kruskal Wallis test. The results showed that the best treatment of cucumber apple shoots was the combination of NAA and BAP, namely the B4N2 treatment (2,5 ppm BAP + 0,20 ppm NAA) with shoot height (0,45 cm). At a single concentration, a concentration of 1 ppm BAP was able to provide a faster effect on shoot formation time, namely at 24 days after initiation (hsi) and the best response to shooting height (0,5cm).